Proportion and clinico-mycological profile of fungal sinusitis in a tertiary care hospital - D., Judit; K., Deepika; Bhaskaran, Gayathri; Jayalakshmi, J.; R., Vijay (International Journal of Research in Medical Sciences, 2026)
Background: Rhinosinusitis is the inflammation of the nose and sinus cavities, which affects about 20% of the population. Earlier considered to be primarily affecting immunocompromised individuals, now increasingly being reported in immunocompetent patients as well. This was a prospective study aimed at evaluating the clinical and mycological profile of fungal sinusitis. Methods: The collected samples were subjected to three methods: KOH mount, LPCB mount, and fungal culture. Results: Out of 128, males were 53.5% and females were 46.4%. The fungal sinusitis contributed to 25%, with a mean age of 46.5 years. A significant association between fungal sinusitis and diabetes mellitus (p<0.0001) was noted. The common factors were agricultural occupation (53%) and monsoon season (35.7%). Nasal obstruction (64.2%) was the predominant symptom. CT scan revealed frequent maxillary and ethmoid involvement. Culture positivity was seen in 21.4%, of which the histopathology correlation was seen in 46.4% of the cases. The fungi isolated were Aspergillus spp., Rhizopus spp., Fusarium spp., and Curvularia spp. Complications like osteomyelitis, adenoiditis, and facial palsy were noted in 21%, and mortality was 3.5%. Conclusions: A higher incidence was noted in middle-aged females, diabetics, and during the monsoon season. Maxillary and ethmoid sinuses were the most frequently affected. Aspergillus species were the predominant pathogens. Early diagnosis and treatment are essential, and it is crucial to employ a combination of diagnostic methods to reach a conclusive result rather than relying solely on a single technique.